App-Guided Exercise Improves Periodontal Status in Periodontitis Treatment - A Pilot Randomized Clinical Trial - Gabriel Guidio Guarenghi; Priscila Alves Teixeira Ribas; Rafael Milani Ferro; Henrique Meister Valenga; Natália Amanda Gomes; Mariana Ortelan Borges; Henrique Kenji Takarada; Tatiana Miranda Deliberador; Iain Chapple; Joao Paulo Steffens (Pesquisa Brasileira em Odontopediatria e Clínica Integrada)
Objective: To compare two protocols for adjunctive exercise prescription – before or after subgingival instrumentation (SI) - during periodontal therapy. Material and Methods: Twenty-four patients were randomly allocated into two groups and evaluated at 3-time points (T0 - Baseline, T1 - 45 days, T2 – 90 days). Group 1 (n=10) received SI at T0, re-evaluation and exercise at T1, and final re-evaluation at T2. Group 2 (n=14) started exercising at T0, received re-evaluation and SI at T1, and final re-evaluation at T2. Clinical parameters included probing depth (PD), clinical attachment loss (CAL), bleeding on probing (BoP), and plaque index. Crevicular fluid was analyzed by multiplex immunoassay. The exercise lasted 7 minutes and was performed 3 times/week using an app. Results: Twenty-four patients completed the study. All clinical parameters improved at T2. Group 2, but not Group 1, significantly improved BoP and CAL at T1. There was no significant interaction or intergroup differences for any clinical parameter. For initial PD≥4mm sites, both groups showed significant reductions in PD and CAL at both time points. Only IL-1β and IFN-γ were significantly reduced for both groups at T2. Conclusion: Both exercise/SI protocols improved periodontal parameters after 90 days.